Susi Pudjiastuti: Kuasa, Dominasi Kharisma dan Kepemimpinan dalam Islam - Addiansyah, Nur Rofiq; Isti’anah, Isti’anah (POLITEA, 2020)
This article will discuss the Indonesian people, the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia in 2014-2019, Susi Pudjiastuti. Susi is a central figure who is able to steal public attention. Various academic writings have been written about the figure of Susi Pudjiastuti, most of which discuss leadership and communication strategies. This paper wants to look deeper into the strength and leadership of Islam. This paper wants to look at the power possessed by Susi, the Domination of Charisma and Islamic Leadership. Susi Pudjiastuti gave a deep picture that women in Islam do not get shackles to do politics. Women get a broad space and leadership skills that are not much different from men. This paper uses a qualitative approach to character studies. The data collection method in this paper is obtained through documentation from time media, books and other literature. Further research that can be done includes the political leadership of Islamic women in the bureaucracy, as well as differences in leadership between men and women.